2018
DOI: 10.1109/tia.2018.2799178
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stator Topologies on Average Torque and Torque Ripple of Fractional-Slot SPM Machines With Fully Closed Slots

Abstract: Abstract-This paper investigates the influence of concentrated winding configurations and stator core structures on torque performance of fractional-slot surface-mounted PM (SPM) machines. From analyzing the separated torque components of prototype SPM machines with 12-slots/10-poles (12S/10P) combination by frozen permeability (FP) method, it can be found that the torque ripple is closely related with local saturation in fully closed slot (FCS) machines. Besides, the heavier local saturation will also jeopard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Fractional slot concentrated winding was used in this study because of its advantages of high torque density and high slot filling coefficient [20]. The slot type of the BWPMTM is equivalent to the closed slot, which can effectively reduce the torque ripple and improve the running performance [21,22]. As shown in Figure 1c, there is a magnetic barrier (the connection between the bottom of the slot and the inner surface of the stator) to maintain the integrity of the stator.…”
Section: Structure and Advantage Analysis Of The Bwpmtm 21 Motor Stru...mentioning
confidence: 99%
“…Fractional slot concentrated winding was used in this study because of its advantages of high torque density and high slot filling coefficient [20]. The slot type of the BWPMTM is equivalent to the closed slot, which can effectively reduce the torque ripple and improve the running performance [21,22]. As shown in Figure 1c, there is a magnetic barrier (the connection between the bottom of the slot and the inner surface of the stator) to maintain the integrity of the stator.…”
Section: Structure and Advantage Analysis Of The Bwpmtm 21 Motor Stru...mentioning
confidence: 99%
“…It can be shown that for maximizing the torque, the width of the teeth with coils in 12S/10P unequal teeth PM machines should be wider, while the width of the teeth with coils in 12S/14P unequal teeth PM machines should be narrower. The issue for using unequal tooth width stator is relatively large torque ripple, which is owing to heavier local saturation [62]. The modular stators in [33], [34], [63], [64] have flux barriers alternately in stator yokes, as shown in Fig.…”
Section: More Electric Aircrafts and Civic Applicationsmentioning
confidence: 99%
“…In the perspective of the machine design‐based methods, optimising the winding distribution to improve the spatial magnetic field is commonly employed [2, 3]. The fractional slot and the skewed slot techniques in the stator are proved to be valid in weakening the cogging torque, even though the average electromagnetic torque can be discounted in some degree [4, 5]. Compared with machine design‐based techniques, the control algorithm‐based methods are more flexible and easier to implement and, therefore, attracts more attention from researchers worldwide.…”
Section: Introductionmentioning
confidence: 99%